Rapid identification of saber steel flexibility, microhardness, and chemical composition by analyzing electromagnetic signatures - Braddock Chen, L. (American Journal of Sports Science, 2020)
Modern fencing sabers are made of composite steel alloys. Although there are regulations standardizing blade dimensions and stiffness, fencers often find blades having variable flexibility and tensile strength from vendor to vendor and, occasionally, from batch to batch of production. Due to the absence of an objective test to assess blade quality, fencers often resort to testing blades with simple visual or physical whip tests. These manual blade assessments, however, are unsatisfactory due to subjective inconsistencies as well as unreliability due to similar blade weights, colors, and appearances. The ability to properly and accurately test blade quality is of utmost importance, not only for competition, but more importantly, to prevent injuries which have occurred as a result of broken blades. Traditional industrial methods of steel alloy identification involve spectrometry or machine tensile strength assessments, which are both destructive to the blade and impractical in a competition arena. We previously reported a method to use the smartphone magnetometer to differentiate fencing steel alloys. This manuscript now demonstrates the correlation between electromagnetic signatures to the flexibility, microhardness and chemical composition of steel blades.